A PROPOSED MODEL OF WEALTH MANAGEMENT IN INDONESIAN ISLAMIC BANKING - Ismail, Nurizal; Riza, Muhammad (Universitas Darrussalam Gontor, 2014)
The Muslim population is expected to increase by 26% to 2030 to approximately 2.2 billion, and currently have a 7.7% share of global GDP which is expected to grow to 8.7% by end 2016. Therefore, the need of wealth management from Islamic way is growing rapidly. Hajj is one of Islamic pillars that Muslim people should concern on it. This hajj is performed depending on the ability of person in term of health and wealth. Moreover, the government plays a major role in management and service of hajj in many Muslim countries. The hajj fund can contribute significantly to economic development of the country. One of the possible mechanisms can be used for managing the hajj fund is by using wealth management as the instrument in managing the fund. Moreover, this study will employs qualitative research that refers to the meanings, concepts, definitions, characteristics, metaphors, symbols and descriptions of the matter understudy by using content and descriptive analysis to get finding of the study. The finding of the study is that the concept of Islamic wealth management differs from Conventional one. It is very comprehensive that cover all philosophical foundation; ontology, epistemology and axiology. Semantically, it is different from the Conventional, because Islamic wealth management has its own paradigm and philosophical underpinning, derived from Qurâan and Sunnah, and secondary source can traced through Islamic literatures such fiqh, tasawwuf, kalam. In practice level, it can be implemented in Indonesian Islamic banking especially in managing the hajj fund to contribute to economic development of ummah.